A new method to study the time correlation between Van Allen Belt electrons and earthquakes. Issue 22 (16th November 2016) - Tao, Dan; Battiston, Roberto; Vitale, Vincenzo; Burger, William J.; Lazzizzera, Ignazio; Cao, Jinbin; Shen, Xuhui
ABSTRACT: A new method to study a possible temporal correlation between hundreds of keV Van Allen Belt electrons and strong earthquakes is proposed. It consists in measuring the electrons pitch angle distribution (PAD), searching for PAD disturbances, and studying the time correlation between these PAD disturbances and strong earthquakes, occurring within a defined time window. The method was applied to measurements of energetic electrons, which were performed with the Energetic Particle, Composition, and Thermal Plasma (ECT)-MagEIS detector on board the Van Allen Probes (VAPs) mission and strong continental earthquakes, with magnitude M 5.0 and hypocenter depth 100 km. We report the correlation studies for electrons with energies of about 350 keV, with which a 3.84 standard deviations correlation peak was found at hour time bin, and about 450 keV with which no correlation peaks above 2.0 standard deviations were found. Our work proves the feasibility of the proposed method and the obtained results add useful and additional information with respect to past studies.